RT-PCR and DNA microarray measurement of mRNA cell proliferation - Rizgar Hassan, Rawaz; Othman Hassan, Abdullah; Farooq Rashid, Rzgar; Ziyad Abdulaqadir, Shang (International Journal of Advanced Engineering, Management and Science, 2021)
For mRNA quantification, RT-PCR and DNA microarrays have been compared in few studies (RT-PCR). Healing callus of adult and juvenile rats after femur injury was found to be rich in mRNA at various stages of the healing process. We used both methods to examine ten samples and a total of 26 genes. Internal DNA probes tagged with 32P were employed in reverse transcription-polymerase chain reaction (RT-PCR) to identify genes (RT-PCR). Ten Affymetrix® Rat U34A cRNA microarrays were hybridized with biotin-labeled cRNA generated from mRNA. There was a wide range of correlation coefficients (r) between RT-PCR and microarray data for each gene. Meaning became genetically unique because of this diversity. Relatively lowly expressed genes had the highest r values. The distance between PCR primers and microarray probes was found to be higher than previously assumed, leading to a drop in agreement between microarray calls and PCR outcomes. Microarray research showed that RT-PCR expression levels for two genes had a "floor effect." As a result, PCR primers and microarray probes that overlap in mRNA expression levels can provide good agreement between these two techniques.